Personalisierte Therapie des Lungenkarzinoms – Stand und Herausforderungen - Riedel, Richard; Wolf, Jürgen (DMW - Deutsche Medizinische Wochenschrift, 2017)
So called „personalized therapy“ has revolutionized the care of non-small cell lung cancer (NSCLC). The discovery of more and more driver mutations in NSCLC has led to a molecular defined sub classification of lung cancer patients. For four driver mutations (EGFRmut, ALKtransl, ROS1transl, BRAF-V600mut) firstline approved drugs are available and became the treatment of choice. Further drugs are in clinical development or can be used as off-label treatment. The emergence of resistance under targeted therapy, the development of new drugs for further driver mutations and the broad implementation of molecular diagnostics for all lung cancer patients are future challenges.
Keywords: Nicht-kleinzelliges Lungenkarzinom (NSCLC); personalisierte Therapie; molekulare Diagnostik